Resistance of melanoma cells to anticancer treatment: a role of vascular endothelial growth factor - Bogusławska-Duch, Joanna; Ducher, Magdalena; Małecki, Maciej (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Melanoma is one of the most aggressive and resistant to treatment neoplasms. There are still many challenges despite many promising advances in anticancer treatment. Currently, the main problem for all types of treatment is associated with heterogeneity. Due to heterogeneity of cancer cells, “precise” targeting of a medicine against a single phenotype limits the efficacy of treatment and affects resistance to applied therapy. Therefore it is important to understand aetiology and reasons for heterogeneity in order to develop effective and long-lasting treatment. This review summarises roles of vascular endothelial growth factor (VEGF) that may stimulate growth of a melanoma tumour irrespective of its proangiogenic effects, contributing to cancer heterogeneity. VEGF triggers processes associated with extracellular matrix remodelling, cell migration, invasion, angiogenesis, inhibition of immune responses and favours phenotypic plasticity and epithelial-mesenchymal transition. Consequently, it participates in mechanisms of interactions between melanoma cancer cells and microenvironment and it can modify sensitivity to therapeutic factors.